2020
DOI: 10.1186/s13148-019-0798-7
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal epigenome-wide association studies of three male military cohorts reveal multiple CpG sites associated with post-traumatic stress disorder

Abstract: Background: Epigenetic mechanisms have been suggested to play a role in the development of post-traumatic stress disorder (PTSD). Here, blood-derived DNA methylation data (HumanMethylation450 BeadChip) collected prior to and following combat exposure in three cohorts of male military members were analyzed to assess whether DNA methylation profiles are associated with the development of PTSD. A total of 123 PTSD cases and 143 traumaexposed controls were included in the analyses. The Psychiatric Genomics Consort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 64 publications
(69 reference statements)
0
44
0
3
Order By: Relevance
“…Implicated in AD 83 Down 0.3241 0.5385 Up 0.0410 0.5904 Up 0.4513 0.5519 V-type proton ATPase subunit F (ATP6V1F) Involved in regulation of luminal or extracellular acidification, a crucial process for the normal physiological function of several organs, implicated in PTSD 42 , 43 Down 0.0613 0.6245 Down 0.0433 0.6486 Down 0.0405 0.6795 Brorin (VWC2) Involves in neural development, implicated in AD 39 Up 0.3971 0.5654 Up 0.0444 0.6572 Up 0.2008 0.6187 Desmoglein-3 (DSG3) Implicated in autoimmune disease 84 Up 0.2187 0.6137 Up 0.0452 0.6081 Up 0.2013 0.5853 DRAXIN Plays an important role in neural development Up 0.3633 0.5632 Up 0.0465 0.5996 Up 0.4593 0.5222 Cadherin-15 (CDH15) May contribute to the sorting of heterogeneous cell types. Implicated in PTSD 85 , cognitive impairment 86 Down 0.9755 0.5105 Down 0.3462 0.5609 Down 0.0024 0.7165 NEDD8-conjugating enzyme UBE2F (UBE2F) Implicated in stress response Up 0.1836 0.5203 Down 0.2715 0.6208 Down 0.0029 0.7572 ...…”
Section: Resultsmentioning
confidence: 99%
“…Implicated in AD 83 Down 0.3241 0.5385 Up 0.0410 0.5904 Up 0.4513 0.5519 V-type proton ATPase subunit F (ATP6V1F) Involved in regulation of luminal or extracellular acidification, a crucial process for the normal physiological function of several organs, implicated in PTSD 42 , 43 Down 0.0613 0.6245 Down 0.0433 0.6486 Down 0.0405 0.6795 Brorin (VWC2) Involves in neural development, implicated in AD 39 Up 0.3971 0.5654 Up 0.0444 0.6572 Up 0.2008 0.6187 Desmoglein-3 (DSG3) Implicated in autoimmune disease 84 Up 0.2187 0.6137 Up 0.0452 0.6081 Up 0.2013 0.5853 DRAXIN Plays an important role in neural development Up 0.3633 0.5632 Up 0.0465 0.5996 Up 0.4593 0.5222 Cadherin-15 (CDH15) May contribute to the sorting of heterogeneous cell types. Implicated in PTSD 85 , cognitive impairment 86 Down 0.9755 0.5105 Down 0.3462 0.5609 Down 0.0024 0.7165 NEDD8-conjugating enzyme UBE2F (UBE2F) Implicated in stress response Up 0.1836 0.5203 Down 0.2715 0.6208 Down 0.0029 0.7572 ...…”
Section: Resultsmentioning
confidence: 99%
“…A longitudinal EWAS for PTSD which meta-analyzed 3 male military cohorts (123 cases and 143 controls) found 3 epigenome-wide significant CpGs-one of which was intergenic while the other 2 were located in genes MAD1L1 and HEXDC . In addition, 12 significant differential methylated regions (DMRs) were found; 4 of these regions were located in the human leukocyte antigen (HLA) and 1 was situated in MAD1L1 ( Snijders et al, 2020 ). Interestingly, as mentioned above in the “common variation” section, a SNP in MAD1LI was associated with PTSD in the largest PTSD GWAS ( Stein et al, 2021 ).…”
Section: Genetic and Environmental Influences In Stress-related Disordersmentioning
confidence: 99%
“…Individuals with PTSD have increased methylation at a CpG site located in Toll-like receptor 8 ( TLR8 ) ( Smith et al, 2011 ), and decreased methylation at CpG sites located in dedicator of cytokinesis 2 ( DOCK2 ) ( Mehta et al, 2017 ), nuclear factor of activated T-cells ( NFATC4 ) ( Hammamieh et al, 2017 ), IL12B ( Bam et al, 2016b ) and aryl hydrocarbon receptor repressor ( AHRR ) ( Logue et al, 2020 ; Smith et al, 2020 ). Prospective studies investigating longitudinal methylation changes associated with PTSD implicated methylation changes in HEXDC and HLA-DPB1 ( Snijders et al, 2020 ), as well as enrichment in IL17 signaling pathway ( Rutten et al, 2018 ).…”
Section: Impact Of Stress On the Immune System In Ptsdmentioning
confidence: 99%
“…The PTSD-associated expression differences in HLA genes are consistent with reports from DNA methylation studies. A longitudinal meta-analysis of three male military cohorts reported that methylation levels across HLA-DPB1 and HLA-DRB1 regions are lower after deployment in individuals with PTSD ( Snijders et al, 2020 ). However, a recent study reported that PTSD was associated with increased methylation across HLA-DPB1 in a civilian cohort of predominantly African American women, whilst the association between PTSD and HLA-DPB1 methylation was in opposite direction in a military cohort of predominantly Caucasian males ( Katrinli et al, 2021 ).…”
Section: Human Leukocyte Antigen (Hla) and Ptsdmentioning
confidence: 99%